Teacher's Emotional Intelligence, Class Management, and School Organizational Climate, on Interaction Behavior among Teachers and Students - Listiyawati Listiyawati; Eliana Sari; Ivan Hanafi (Syntax Corporation Indonesia, 2022)
The problems of classroom interaction among teachers and students arise in conditions of academic demands that assume the practice of teachers' social competence in class. This paper aims to study the effect of teachers' emotional intelligence, classroom management, and school organization climate on interaction behavior among teachers and students in SPK High School. A survey method with path analysis was applied to test the hypothesis and conduct interviews among 105 teachers and students by proportional random sampling technique. Upon this research, the conclusion is obtained. (1) A teacher's emotional intelligence, class management, and school organization climate positively affect teacher and student interaction behavior. (2) A teacher's emotional intelligence has a positive direct effect on school organization climate. Class management has a positive direct effect on the school organization climate. (3) A teacher's emotional intelligence has a positive direct effect on class management. (4) A teacher's emotional intelligence positively affects teacher and student interaction behavior through the school organization climate. (5) Class management positively impacts teacher and student interaction behavior through the school organization climate. The conclusion is that the teacher and student interaction behavior is affected by the teacher's emotional intelligence, class management, and school organization climate